Keanekaragaman Jenis Semut (Hymenoptera: Formicidae) di Hutan Adat Guguk Kabupaten Mrangin Provinsi Jambi - Fajar Ahmad; Apriza Hongko Putra; Rivo Yulse Viza (BIOCOLONY, 2019)
This study aims to determine the diversity of ants in Hutan Adat Guguk. Research type applied is descriptive quantitative research. This study was conducted on April 2018, in two stages. The first stages is sampling which is done in the Hutan Adat Guguk by making four plots. The second stage is identification of ants carried out by purposive sampling technique, which is by considering the type of vegetation and altitude. The method used is bait trap, pitfall trap, and hand collecting. Collected samples were analyzed with Shannon-Wiener diversity index (H`), index of richeness (DMg), and evennes index (E). The result showed the ants with 2633 individuals were clasified in to 22 species, consisting of 7 genera and 3 subfamilies. The result of data analysis showed the value of the Shannon-Wiener diversity index (H`) is 2,21 (medium criteria), index of richeness (DMg) is 17,05 (high criteria), and evennes index (E) is 0,41 (stable criteria).